2016
DOI: 10.1158/1535-7163.mct-15-0707
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA PVT1 Promotes Non–Small Cell Lung Cancer Cell Proliferation through Epigenetically Regulating LATS2 Expression

Abstract: Long noncoding RNAs (lncRNA) are a novel class of transcripts with no protein coding capacity, but with diverse functions in cancer cell proliferation, apoptosis, and metastasis. The lncRNA PVT1 is 1,716 nt in length and located in the chr8q24.21 region, which also contains the myelocytomatosis (MYC) oncogene. Previous studies demonstrated that MYC promotes PVT1 expression in primary human cancers. However, the expression pattern and potential biologic function of PVT1 in non-small cell lung cancer (NSCLC) is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
180
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(189 citation statements)
references
References 45 publications
(40 reference statements)
6
180
0
1
Order By: Relevance
“…Previous studies have reported that PVT1 was significantly upregulated in NSCLC and promoted cell proliferation, migration and invasion, and inhibited apoptosis of NSCLC cells [15, 35]. Consistently, the present study confirmed the abnormal high expression of PVT1 in NSCLC tissues and cells.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported that PVT1 was significantly upregulated in NSCLC and promoted cell proliferation, migration and invasion, and inhibited apoptosis of NSCLC cells [15, 35]. Consistently, the present study confirmed the abnormal high expression of PVT1 in NSCLC tissues and cells.…”
Section: Discussionsupporting
confidence: 91%
“…A meta-analysis by Liu et al also suggested that the up-regulation of PVT1 predicted lymph node metastasis and a worse OS in cancer patients, although the association between PVT1 and other clinicopathological parameters was not discussed [15]_ENREF_15. In addition, other publications since 2015 have continued to investigate the association between PVT1 expression and the prognosis of cancer patients [13, 14, 26-35]. To reach a more convincing conclusion and explore the potential mechanism of action of PVT1 in tumors, we performed the current study by merging the results of published studies and TCGA survival data and conducting GO and KEGG analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have demonstrated that PVT1 could promote proliferation, migration and invasion of cancer cells. Studies also observed that the level of PVT1 expression was higher in tumor tissues than in adjacent non-cancerous tissues and correlated with a poor prognosis [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, Wan et al . found that the lncRNA plasmacytoma variant translocation 1 (PVT1) promoted NSCLC proliferation by epigenetically regulating large tumor suppressor kinase 2 (LATS2) expression [10]. LncRNA- urothelial carcinoma-associated 1 (UCA1) exerts oncogenic functions in NSCLC by targeting miR-193a-3p [11].…”
Section: Introductionmentioning
confidence: 99%